Antimicrobial susceptibility of indicator bacteria isolated from chickens in Southeast Asian countries (Vietnam, Indonesia, and Thailand) - Usui, M.; Ozawa, S.; Onozato, H.; Kuge, R.; Obata, Y.; Uemae, T.; Ngoc, P.T.; Heriyanto, A.; Chalemchaikit, T.; Makita, K.; Muramatsu, Y.; Tamura, Y. (Japanese Society of Veterinary Science, 2014)
To determine the prevalence of indicator bacteria resistant to antimicrobials among poultry in three Southeast Asian countries (Vietnam, Indonesia and Thailand), we examined the antimicrobial susceptibilities of commensal bacteria isolated from chickens. In total, 125, 117 and 180 isolates of Escherichia coli, Enterococcus faecalis and Enterococcus faecium, respectively, were used to test for antimicrobial susceptibility. Bacterial resistance to antimicrobial treatment was most frequently observed with oxytetracycline with a prevalence of 73.6% (E. coli), 69.2% (E. faecalis) and 92.2% (E. faecium). Resistance to fluoroquinolones, which are critically important medicines, was also frequently observed in E. coli (48.8%), E. faecalis (17.9%) and E. faecium (82.8%). The prevalence of indicator bacteria resistant to most of the antimicrobials tested in these countries was higher than those for developed countries. The factors underlying antimicrobial resistance may include inappropriate and/or excessive use of antimicrobials. These results highlight the need for monitoring the emergence and prevalence of antimicrobial resistance in developing countries.